A Heart Beating Hard - Goodman, Lauren Foss (Book collections on Project MUSE., 2015)
A Heart Beating Hard is about looking long and deep into the invisible life of a person we too often pass by. It is the story of Marjorie, who works in the Store and does her best to go on with the days; of Margie, growing up in Apartment #2 with the sounds of Ma and Gram and Him all around; and of Marge, who should never have been, who should have been helped. In A Heart Beating Hard, we see how Marjorie manages to go on with the days, how even in the bright lights and grabbing hands of the outside world, inside, Marjorie knows how to take care of her self and her secrets. It is a story about the passed-along People, about how we are the same and how we are different, about how we become who we are and how we protect our most private places from the cold glare of all that we cannot control.